The relationship between fluid restriction compliance and quality of life in chronic kidney failure patients undergoing hemodialysis - Putri Yunitasari; Murtaqib Murtaqib; Rondhianto Rondhianto; Farida Nur Qomariyah (Nursing and Health Sciences Journal (NHSJ), 2026)
Chronic kidney disease (CKD) necessitates stringent fluid restriction during hemodialysis to prevent volume overload, yet its direct impact on patient-reported outcomes remains inadequately characterized in regional healthcare settings. This study investigated the association between adherence to fluid restriction and health-related quality of life (HRQoL) among maintenance hemodialysis patients. A cross-sectional design was utilized with 84 participants systematically selected via simple random sampling from a cohort of 160 at a regional Indonesian referral hospital in January 2026. Fluid compliance and HRQoL were quantified using the validated Fluid Control and Dietary Compliance Questionnaire (FCDCQ) and Kidney Disease Quality of Life-36 (KDQOL-36), respectively, and bivariate relationships were evaluated using Spearman’s rank-order correlation, following institutional ethical approval. Most respondents demonstrated satisfactory fluid compliance and reported moderate overall HRQoL. Statistical analysis revealed a significant positive correlation between fluid restriction adherence and HRQoL (ρ = 0.348, p < 0.001), indicating that greater compliance is associated with improved patient-reported well-being. However, the modest effect size underscores the multifactorial nature of wellness in end-stage renal disease. Fluid management constitutes a critical, modifiable behavioral determinant of HRQoL. Integrating structured, nurse-led adherence counseling and continuous psychological support into routine dialysis care can simultaneously optimize clinical stability and psychosocial adaptation. Longitudinal studies employing objective monitoring technologies are recommended to validate causal pathways and refine comprehensive patient management frameworks.